RANCANG BANGUN SIMULATOR DESALINATION PLANT JENIS SINGLE STAGE - Agus Sukandi; Angga Aprianto; Arief Eka Putra; Halimatussa’diyah Halimatussa’diyah (Politeknik Negeri Jakarta, 2017)
ABSTRACTDesalination Plant is an instrument that can convert the water containing high salt (sea water) to water containing low salt (fresh water) through evaporation process which can be shown by the value of electric conductivity. One of the simplest Desalination Plant type is a single stage type Desalination Plant. The purpose of this design is to make the Desalination Plant simulator as a learning media in the Energy Conversion Engineering Laboratory, which is expected to facilitate the students in understanding the material of Desalination Plant system on a power plant system. The design of the tool consists of two parts: evaporator and condenser. The renewal of the desalination plant design makes the design of desalination plant using heater system heater then make condenser which consists of cooling pipes that will condense the evaporated vapor into fresh water. With this system obtained output of fresh water that can be utilized in daily needs (can be drunk).Test of performed by adjusting the variation of condenser flow and volume of heating water to find out how much water is produced desalination plant process.Keywords : Desalination Plant, Single Stage, Evaporation, Condensation, Heater.ABSTRAKDesalination Plant adalah suatu alat yang dapat mengolah air yang mengandung kadar garam tinggi (air laut) menjadi air yang mengandung kadar garam rendah (air tawar) melalui proses evaporasi yang dapat ditunjukkan dengan nilai electric conductivity. Salah satu jenis Desalination Plant yang sederhana adalah Desalination Plant jenis single stage. Tujuan dari rancang bangun ini adalah membuat simulator Desalination Plant sebagai media pembelajaran di Laboratorium Teknik Konversi Energi, yang diharapkan dapat mempermudah mahasiswa dalam memahami materi sistem Desalination Plant pada Sistem Pembangkit listrik. Perancangan alat terdiri dari dua bagian yaitu evaporator dan kondensor. Keterbaruan dari rancang bangun Desalination Plant ini membuat rancang bangun Desalination Plant dengan menggunakan sistem pemanas heater kemudian membuat kondensor yang terdiri dari pipa-pipa pendinginan yang akan mengkondensasi uap hasil evaporasi menjadi air tawar. Dengan sistem inilah didapatkan output berupa air tawar yang dapat dimanfaatkan dalam kebutuhan sehari-hari (dapat diminum). Pengujian dilakukan dengan mengatur debit aliran kondensor dan volume air laut yang dipanaskan untuk mengetahui seberapa banyak air yang dihasilkan dari proses desalination plant.Kata Kunci : Desalination Plant, Single Stage, Evaporasi, Kondensasi, Heater.